Diverse group of smartphone users and their shopping activities - Bacik, Radovan; Kakalejcik, Lukas; Gavurova, Beata (Univerzita Pardubice, 2018)
The analysis of customers’ purchasing activities, their preferences and future potential are the subject of interest of many experts in the field of marketing. Smartphones became the common devices used during purchasing process. By examining purchasing behavior of smartphone owners, the valuable insights useful for modeling new selling strategies could be mined. The main objective of this study is to analyze different behavioral patterns of smartphone users during the pre-purchase stage of the purchase process. To achieve these goal, we analyzed the data from Consumer Barometer containg data for 56 countries and 78,920 respondents. We created 3 new latent variables – factors - while reducing the number of variables (11) entering the cluster analysis by using factor analysis. Subsequently, using the cluster analysis and the method of k-medians, we created four clusters of users. Even though there are more active and less active clusters, the most popular activities involved getting store directions and checking where to buy a certain product. Users from European countries (represented by Cluster 1 and 2) use smartphones in the prepurchase process very little, showing conservative approach towards smartphones in these countries. On the other hand, users in Cluster 3 and 4 seem to be the most active smartphone users in terms of purchasing process.
Keywords: smartphone user; mobile shopping; mobile-first; k-medians; cluster analysis; M31; M15